Equal educational policies in Spain. Gender equality in teaching studies - Teresa González-Pérez (Arizona State University, 2018)
Gender equality is a fundamental principle in democratic societies and in the development of the education system. In this sense gender equality it has been part of European policies developed since the late 20th century. During the implementation process of the European Higher Education Area, the goal of reducing inequalities between women and men in higher education was formulated. The aim of this work is to study gender equality in studies of teaching in democratic Spain. This research follows the methodology of legislative analysis; we conducted a tour of the main laws that affect equality and its realization in the curriculum, as well as the theoretical review of the inclusion of a gender perspective in initial teacher training. We analyze legislation and teaching curricula to conclude the reflection on the changing trends. In the second decade of the century inequality persists in education through various forms, from socialization to stereotypes, the hidden curriculum and teaching materials. The formation of teachers is one of the keys to eliminating gender inequality, although not a major aspect in their learning. The legal framework has not been developed enough to solve this problem, since the legislation has not been explicit. Universities are constantly changing, but the university has done little to introduce changes relating to equal training, to consider gender bias in programs, and to recognize sexism in the classroom, and as such, face significant challenges to solve inequality.